Different Problem, Same Solution: Contract‐Specialization in Venture Capital. Issue 2 (June 2014) - Bengtsson, Ola; Bernhardt, Dan
<x xml:space="preserve">Abstract</x> Real‐world financial contracts vary greatly in the combinations of cash flow contingency terms and control rights used. Extant theoretical work explains such variation by arguing that each investor finely tailors contracts to mitigate investment‐specific incentive problems. We provide overwhelming evidence from 4, 561 venture capital (VC) contracts that this tailoring is overstated: even though there is broad variation in contracting across VCs, each individual VC tends to specialize, recycling familiar terms. In fact, a VC typically restricts contracting choices to a small set of alternatives: 46% of the time, a VC uses the same exact cash flow contingencies as in one of her previous five contracts. We document specialization in both aggregated downside protection, and in each individual cash flow contingency term. Such specialization remains economically and statistically significant even after controlling for VC and company characteristics. We also find that VCs learn to use new contractual solutions from other VCs in her syndication network. Our findings challenge the traditional premise that each investor selects from the universe of combinations of terms to match an investment's unique contracting problem. Rather, the cumulative evidence indicates that contract‐specialization arises because investors better understand payoff consequences of familiar terms, and are reluctant to experiment with unknown combinations.